Strategic Applications and the Challenges of Subcritical Water Extraction Technology in Food Industries - Erasto Mlyuka (Science Faculty of Chiang Mai University, 2019)
Extraction is a required step for the utilization of most natural bioactive compounds in food, pharmaceutical and cosmetic industries. A green subcritical water extraction (SWE) technique for the extraction of bioactive compounds has been of great interest in recent years. The utilization of clean extraction solvent (subcritical water) in food and pharmaceutical industries has attracted public and scientific interest, due to its tunable polarity at different temperatures above its boiling point. SWE technique uses subcritical water with wide range of polarities attained by temperature programming which enables the selective extraction of polar, moderately polar, and nonpolar bioactive compounds from natural sources (plant or animal origin). Natural sources are the promising source of safe bioactive compounds. Extracts from these sources using subcritical water can be directly used for food and pharmacological purposes. However, to exploit these resources at a commercial scale, relevant strategies for their extraction must be developed. This review addresses the unique characteristics of subcritical water, the principal applications of SWE, parameters influencing the extraction yield and selectivity, engineering scale-up and bio products extraction strategies to ascertain the stability of bioactive compounds in subcritical water conditions and challenges facing the prospect of this technology.